Green coke and long-cycle-performance artificial graphite as well as preparation method and application of green coke and long-cycle-performance artificial graphite

By graphitizing the raw coke of specific conditions, artificial graphite with long cycle performance is prepared, which solves the problem of poor performance of artificial graphite in the negative electrode materials of lithium-ion batteries in the prior art, and achieves better cycle performance and service life.

CN119503758APending Publication Date: 2025-02-25HUNAN SHINZOOM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311062852.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The artificial graphite in the prior art has the problem of poor long cycle performance in lithium-ion battery anode materials, which limits its wide application.

Method used

By using raw coke that meets specific conditions as raw materials and performing graphitization treatment, artificial graphite with long cycle properties was prepared. In the solid nuclear magnetic resonance spectrum of pyrogenic carbon, the ratio of the peak area of ​​alkyl carbon to the peak area of ​​aromatic carbon is less than 0.4%, and the oxygen fine spectrum treatment of X-ray photoelectron energy spectrum is less than 1.0%, so as to reduce the formation of the internal pore structure.

Benefits of technology

It significantly improves the long cycle performance of artificial graphite in lithium-ion batteries, reduces capacity attenuation, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503758A_ABST
    Figure CN119503758A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy, and particularly relates to green coke and long-cycle performance artificial graphite as well as a preparation method and application thereof. According to the invention, the green coke meeting specific requirements is used as a raw material for graphitization to prepare the graphite, the graphite is used as the negative electrode material of the lithium ion battery, the capacity attenuation in the cycle process of the lithium ion battery is reduced, and the graphite has better long cycle performance. As the side chain structures of the green coke raw materials meeting specific conditions are reduced, the influence on the accumulation of graphite sheets in the graphitization process of the green coke raw materials is reduced; in addition, the content of heteroatoms such as N, S and the like in the green coke is low, so that gas escape in the graphitization process is reduced, and pores in the graphite are few. According to the graphite, an SEI film is stable in the circulation process, the death lithium retention condition is reduced, the capacity fading caused by SEI film regeneration and death lithium retention is improved, and the graphite has good long-cycle performance when being used as a negative electrode of a lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy, and in particular relates to a coke-producing, long-cycle performance artificial graphite and a preparation method and application thereof. Background Art

[0002] In the prior art, the preparation method of artificial graphite negative electrode materials generally uses petroleum coke, needle coke and asphalt coke as raw materials, crushes the raw materials, and then performs carbonization and graphitization treatment to obtain them. However, the artificial graphite prepared by the prior art has disadvantages such as poor long-cycle performance due to its own internal structural defects, which limits its wide application in lithium-ion battery negative electrode materials. In order to improve the performance of graphite negative electrode materials, the main graphite modification methods reported are: surface oxidation and reduction treatment, doping and coating treatment, etc. However, these methods are post-processing methods, which increase the process flow. Summary of the invention

[0003] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects of artificial graphite in the prior art, thereby providing an artificial graphite with coke-producing and long cycle performance and a preparation method and application thereof.

[0004] To this end, the present invention provides the following technical solutions:

[0005] The present invention provides a raw coke, which satisfies the following conditions:

[0006] In the solid nuclear magnetic resonance spectrum, the ratio of the peak area of ​​alkyl carbon to the peak area of ​​aromatic carbon is less than 0.4%.

[0007] In the present invention, the alkyl carbon refers to an sp3 hybridized carbon atom (such as -CH3); the aromatic carbon refers to an sp2 hybridized carbon atom (such as a carbon atom on an aromatic ring).

[0008] Optionally, in the solid nuclear magnetic resonance spectrum, the chemical shift of the alkyl carbon is 10-20 ppm; and / or, the chemical shift of the aromatic carbon is 100-150 ppm.

[0009] Optionally, the coke further satisfies the following conditions:

[0010] The oxygen fine spectrum of the X-ray photoelectron spectrum is subjected to peak separation, and the obtained S1 / S is less than 1.5%, preferably less than 1.0%, wherein S1 is the area of ​​the peak at the position of 530 eV±0.5 eV, and S is the total area of ​​the peaks in the range of 529-536 eV;

[0011] And / or, in the full spectrum of X-ray photoelectron spectroscopy, the ratio of the peak area of ​​heteroatoms other than O atoms to the total peak area is less than 1.8%, preferably less than 1.0%.

[0012] Optionally, the green coke has a coarse mosaic structure, a fine mosaic structure, or a fibrous structure; preferably, it has a coarse mosaic structure.

[0013] In the present invention, the mosaic structure is a granular distribution of crystal units of petroleum coke under a polarizing microscope, wherein a unit size of less than 1.0 μm is a fine mosaic, and a unit size between 5.0 and 10.0 μm is a coarse mosaic. The fiber structure is a crystal unit size with a width of less than 10.0 μm and a length between 10.0 and 30 μm, which seems to flow in one direction.

[0014] The present invention also provides a method for preparing artificial graphite with long cycle performance, which uses the above-mentioned raw coke as a raw material and performs graphitization.

[0015] Optionally, the graphitization temperature is 2900-3200° C., and the graphitization time is 2-3 h;

[0016] Optionally, the step of crushing the raw coke is further included before graphitization; the D of the crushed material is controlled. 50 The particle size is 10-16μm.

[0017] Optionally, the green coke includes at least one of petroleum coke, needle coke, and pitch coke;

[0018] Optionally, the raw coke is derived from a delayed coking process. The present invention has no particular requirements on the raw materials for delayed coking, and typically, but not limitingly, petroleum / coal refining byproducts can be used as raw materials to obtain raw coke through delayed coking.

[0019] The present invention also provides an artificial graphite material with long cycle performance, which is prepared by the above-mentioned preparation method.

[0020] The present invention also provides a lithium ion battery negative electrode material, comprising the above-mentioned artificial graphite with long cycle performance.

[0021] In the present invention, the negative electrode material of the lithium-ion battery can be pure artificial graphite prepared by the above method, or it can be a modified material, for example, after surface oxidation and reduction treatment, doping and coating treatment, etc.

[0022] The present invention also provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode material.

[0023] In the present invention, the specific composition and preparation method of the lithium-ion battery are conventional in the art. Typically and non-limitingly, the lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, which are conventional in the art.

[0024] Typically, but not limiting, the preparation method of the lithium-ion battery includes: mixing graphite with styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), and conductive carbon black (SP) in a ratio of 95.5:2:1.5:1, coating it on a copper foil, drying and rolling it to prepare a negative electrode sheet, and assembling it with a metal lithium sheet into a button battery.

[0025] The technical solution of the present invention has the following advantages:

[0026] The method for preparing artificial graphite with long cycle performance provided by the present invention is prepared by graphitizing raw coke, wherein the raw coke meets the following conditions: in the solid nuclear magnetic resonance spectrum, the ratio of the peak area of ​​alkyl carbon to the peak area of ​​aromatic carbon is less than 0.4%. The graphite prepared by graphitizing raw coke that meets specific requirements as a raw material is used as a negative electrode material for lithium ion batteries, and the capacity decay is reduced during the cycle of the lithium ion battery, and has good long cycle performance. This is because the side chain structure in the raw coke material that meets the specific conditions is reduced, which reduces the impact of the stacking of graphite sheets during its graphitization process, reduces the structural defects of the graphite material itself, and the SEI film of the graphite is stable during the cycle, and the retention of dead lithium is reduced. The capacity decay caused by SEI film regeneration and retention of dead lithium is improved, and the graphite has good long cycle performance when used as the negative electrode of the lithium battery.

[0027] The invention provides a method for preparing artificial graphite with long cycle performance. The method comprises the following steps: performing peak separation processing on the oxygen fine spectrum of the X-ray photoelectron spectrum, and obtaining an S1 / S of less than 1.0%, wherein S1 is the area of ​​the peak at the position of 530 eV±0.5 eV, and S is the total area of ​​the peaks in the range of 529-536 eV. The reason for such limitation is that: S1 is a characteristic peak of inorganic oxygen, and this part of the material has strong thermal stability and a high cracking temperature. When this part of the material is cracked, a pseudo-graphite phase is formed, and the structure is solidified. The pores caused by the gas generated by the cracking of the inorganic oxygen are not easy to be further repaired, and the low content of the inorganic oxygen can avoid the formation of internal pores (internal defects), thereby further improving the cycle performance of the material.

[0028] In the preparation method of artificial graphite with long cycle performance provided by the present invention, in the full spectrum of X-ray photoelectron spectrum, the ratio of the peak area of ​​heteroatoms other than O atoms to the total peak area is less than 1.0%. With this definition, the content of heteroatoms such as N and S in the raw coke is small, so that gas escape is reduced during the graphitization process, the formation of internal pore structure is reduced, and the obtained graphite has the characteristics of few internal pores (few self-structural defects), which further improves the long cycle performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 is the solid NMR image of the coke described in Example 1 of the present invention;

[0031] Figure 2 is the solid NMR image of the coke described in Comparative Example 1 of the present invention;

[0032] Figure 3 is the X-ray photoelectron spectroscopy oxygen spectrum of the coke described in Example 1 of the present invention;

[0033] Figure 4 It is the X-ray photoelectron spectrum oxygen spectrum of the coke described in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0035] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0036] Example 1

[0037] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (asphalt coke), the specific composition of the raw coke material and the D 50 The particle sizes are shown in Table 1 below. Figure 1 is the solid NMR image of the raw material pitch coke in this embodiment, Figure 3 It is the X-ray photoelectron spectroscopy oxygen spectrum of the raw material pitch coke in the present application. The raw coke is graphitized at 3090° C. for 2 hours to obtain the graphite material.

[0038] Example 2

[0039] This embodiment provides a method for preparing artificial graphite with long cycle performance. The specific preparation method is as follows: crushing raw coke (petroleum coke) raw materials, and the specific composition of the raw coke raw materials and the D50 The particle sizes are shown in Table 1 below. The green coke is graphitized at 3090° C. for 2 hours to obtain the graphite material.

[0040] Example 3

[0041] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50 The particle sizes are shown in Table 1 below. The green coke is graphitized at 3200° C. for 2.5 hours to obtain the graphite material.

[0042] Example 4

[0043] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50 The particle sizes are shown in Table 1 below. The green coke is graphitized at 2950° C. for 3 hours to obtain the graphite material.

[0044] Example 5

[0045] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (needle coke), the specific composition of the raw coke material and the D 50 The particle size is shown in Table 1 below. The green coke is graphitized at 3090° C. for 2 hours to obtain the graphite material.

[0046] Example 6

[0047] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50 The particle size is shown in Table 1 below. The green coke is graphitized at 3090° C. for 2 hours to obtain the graphite material.

[0048] Example 7

[0049] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50 The particle size is shown in Table 1 below. The green coke is graphitized at 3090° C. for 2 hours to obtain the graphite material.

[0050] Example 8

[0051] This embodiment provides a method for preparing artificial graphite with long cycle performance, and the specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50The particle size is shown in Table 1 below. The green coke is graphitized at 3090° C. for 2 hours to obtain the graphite material.

[0052] Comparative Example 1

[0053] This comparative example provides a method for preparing artificial graphite with long cycle performance. The specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50 The particle size is shown in Table 1 below. The green coke is graphitized at 3000° C. for 2 h to obtain the graphite material.

[0054] Comparative Example 2

[0055] This comparative example provides a method for preparing artificial graphite with long cycle performance. The specific preparation method is: crushing the raw coke material (petroleum coke), the specific composition of the raw coke material and the D 50 The particle size is shown in Table 1 below. The green coke is graphitized at 3000° C. for 2 h to obtain the graphite material.

[0056] Test Case

[0057] The raw coke and the prepared graphite material of each embodiment and comparative example were subjected to performance tests, and the specific test methods are as follows:

[0058] Raw coke NMR characterization method and peak attribution: Solid NMR carbon spectrum was tested using a Bruker NMR spectrometer, and the test conditions were: sampling time 0.03s, cycle delay time 2s, test 1h. The carbon spectrum peak distribution obtained by the test was: 10-20ppm (alkyl carbon), 30-60ppm (CO), 100-150ppm

[0059] (Aromatic carbon), 190-220 ppm (C=O).

[0060] XPS characterization method and peak attribution, peak area calculation: Thermo Fisher X-ray photoelectron spectrometer was used for testing, and the test conditions were: Al Kα ray (hv = 1486.6 eV) was selected as the X-ray source excitation source, beam spot 400um, full spectrum scan: pass energy of 150 eV, step length 1 eV, narrow spectrum scan: pass energy of 50 eV, step length 0.1 eV. XPS processing software was used to perform peak fitting on the spectrum. Among them, after peak fitting, the peaks of the oxygen spectrum were assigned as follows: 530.5 eV (inorganic oxygen), 531.7 eV (CO), 532.8 eV (C = O), 534 eV (COO), S1 is the area of ​​the peak at 530 eV ± 0.5, S is the total area of ​​the peaks in the range of 529-536 eV, and the S1 / S value was calculated.

[0061] The specific method of making graphite into batteries is: mix graphite with SBR, CMC, and SP in a ratio of 95.5:2:1.5:1, apply it on copper foil, dry and roll it to prepare the negative electrode sheet, and assemble it with electrolyte LBC315-T9 and metal lithium sheet into CR2016 button battery.

[0062] The test method of cycle performance is as follows: in a 25℃ constant temperature box, the battery is charged at 1C to 4.2V and then stopped at 0.05C; left for 5 minutes; discharged at 1C to 3.0V; the cycle is completed after 1000 cycles, and an extension line is made on this basis to predict its cycle performance.

[0063] Test method for graphitization degree: X-ray diffraction test d002, according to graphitization degree = (0.344-d 002 ) / (0.344-0.3354) formula.

[0064] Testing method for specific surface area: Use the static method to calculate the BET specific surface area of ​​the sample based on the nitrogen adsorption-desorption curve.

[0065] The testing method of tap density is as follows: Use a tap density meter to test, with a vibration frequency of 250 Hz and a vibration number of 1000. Record the volume V and calculate it according to the formula: tap density = M (sample mass) / V (volume of sample after tapping).

[0066] 5T compaction density test method: Use a compaction density meter to test the density of the sample under a pressure of 5T.

[0067] The parameters of the raw material coke in each embodiment and comparative example are shown in Table 1, and the specific test results of the obtained graphite material are shown in Table 2:

[0068] Table 1 Coke raw material parameters

[0069]

[0070] Table 2 Graphite material parameters

[0071]

[0072]

[0073] It can be seen from the test results in the above table that the embodiments of the present invention can reduce the structural defects of the graphite material itself, significantly improve the cycle performance of the material, and extend the service life by making the coke raw materials meet specific requirements compared with the comparative example; by comparing Examples 6-8 with other embodiments, it can be seen that by limiting the ratio of the peak area of ​​heteroatoms other than O atoms in the coke raw materials to the total peak area and S1 / S, the cycle performance of the material can be further improved.

[0074] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A raw coke, characterized in that: The coke production meets the following conditions: In the solid nuclear magnetic resonance spectrum, the ratio of the peak area of ​​alkyl carbon to the peak area of ​​aromatic carbon is less than 0.4%.

2. The raw coke according to claim 1, characterized in that In the solid-state NMR spectrum, the chemical shift of the alkyl carbon is 10-20 ppm; and / or, the chemical shift of the aromatic carbon is 100-150 ppm.

3. The raw coke according to claim 1 or 2, characterized in that: The coke also meets the following conditions: The oxygen fine spectrum of the X-ray photoelectron spectrum is subjected to peak separation, and the obtained S1 / S is less than 1.5%, preferably less than 1.0%, wherein S1 is the area of ​​the peak at the position of 530 eV±0.5 eV, and S is the total area of ​​the peaks in the range of 529-536 eV; And / or, in the full spectrum of X-ray photoelectron spectroscopy, the ratio of the peak area of ​​heteroatoms other than O atoms to the total peak area is less than 1.8%, preferably less than 1.0%.

4. The raw coke according to any one of claims 1 to 3, characterized in that The raw coke has a coarse mosaic structure, a fine mosaic structure, and a fibrous structure; Preferably, it is a coarse mosaic structure.

5. A method for preparing artificial graphite with long cycle performance, characterized in that: The raw coke according to any one of claims 1 to 4 is used as a raw material and graphitized.

6. The method for preparing artificial graphite with long cycle performance according to claim 5, characterized in that: The graphitization temperature is 2900-3200°C, and the graphitization time is 2-3h; Optionally, the step of crushing the raw coke is further included before graphitization; Optionally, control the D of the crushed material 50 The particle size is 10-16μm.

7. The method for preparing artificial graphite with long cycle performance according to claim 5 or 6, characterized in that: The green coke includes at least one of petroleum coke, needle coke and pitch coke; Optionally, the raw coke comes from a delayed coking process.

8. A long cycle performance artificial graphite, characterized in that: The method is prepared according to any one of claims 5 to 7.

9. A negative electrode material for a lithium ion battery, characterized in that: Including the long cycle performance artificial graphite as described in claim 8.

10. A lithium ion battery, characterized in that: The negative electrode material for a lithium-ion battery comprises the negative electrode material of claim 9.